(3TLQI GdfSH GdTQja GdfHhis - (3EHQGgje Hf jMji GdMSjfjs ((3egOi Hf YHO GdeWdH GHf GdeQJVi GdMSjfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Hjf ddCee HHjGf QShdg SjO GdYQH hGdYLe eG ajg CMJdahG , hCRU dge fgL GdgOi aSdchg HYO Cef cGfhG Ydi MGFQ GdQOi YcahG s
(3BNQgG (B:s
(3Gddge GLYd eG CdafGg NGdUkG dhLgc GdcQje gPG BNQ GdfSH GdTQja GdWGgQ s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B246 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJGQjNs